The development of business case framework for introducing the set-based concurrent engineering application. - Mohd Maulana, Muhd Ikmal Isyraf Bin (Cranfield University, 2018)
Product development challenges have put such an immense pressure to the companies to become more competitive and efficient in the market. The key demand is sustaining the design through product innovation, produce a quality product, shorten the lead time and in a cost-effective manner. Lean Product Development (LeanPD) through the Set-Based Concurrent Engineering (SBCE) is an approach that has these capabilities, including providing a suitable knowledge environment to support decision making throughout the development process. SBCE provides an environment where the design space is explored thoroughly which leads to enhanced innovation. This is done by considering an alternative set of solutions after gaining the knowledge to narrow down the solutions until the optimal solution is reached. However, the successful measures of the SBCE applications in practice are still ambiguous. To overcome this, the author believed that having a business case is the way to demonstrate and justify the benefits comes from the application of the SBCE. This thesis presents a process of developing business case framework for introducing the application of SBCE which enable the justification of the SBCE benefits, hence improve the confidence of having the SBCE in the company. The structure of the framework presents a generic guideline of having a business case in SBCE by justifying the benefits of its application.
Keywords: Business case; lean product development; set-based concurrent engineering; lean thinking; framework; knowledge creation